2005
DOI: 10.1080/00365520510015692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of precancerous and other metaplasia in the distal oesophagus and gastro-oesophageal junction

Abstract: While BO is not common among Swedish gastroscopy patients, IM and PAM are found in every 7th and 6th patient, respectively. Age-dependent increments in prevalence suggest that not only BO and IM, but also cardia-type mucosa are acquired and/or progressive lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
2
46
1
2
Order By: Relevance
“…BE has been detected in ∼ 15% of patients with chronic GERD ( 26 ) and in ∼ 1-2% of population subjects ( Table 2 ) ( 27,28 ). In a population-based study from Sweden, the authors found that severe and chronic GERD were risk factors for the development of EAC; however, 40% of the cohort with esophageal cancer reported no prior history of GERD symptoms ( 29 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…BE has been detected in ∼ 15% of patients with chronic GERD ( 26 ) and in ∼ 1-2% of population subjects ( Table 2 ) ( 27,28 ). In a population-based study from Sweden, the authors found that severe and chronic GERD were risk factors for the development of EAC; however, 40% of the cohort with esophageal cancer reported no prior history of GERD symptoms ( 29 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Öberg et al [28] and Csendes et al [7] recently reported presence of IM within endoscopic short-segment CLE of 30.5% and 35%, respectively. In investigation of individuals with and without GERD symptoms, Johansson et al [29] recently found the incidence of IM in the absence and presence of endoscopically visible CLE to be 12% and 36%, respectively. Thus the data obtained in our study are in line with recent reports.…”
Section: Discussionmentioning
confidence: 97%
“…Presence of IM within endoscopic short-segment CLE (≤ 3cm) has been variously reported to be 13% [42], 30.5% [12] and 35% [28]. Johansson et al [43] recently reported the incidence of IM in the absence and presence of endoscopically visible CLE as 12% and 36%, respectively. Lenglinger et al [21] recently found IM in 27.5% of GERD patients with CLE < 3 cm.…”
Section: Discussionmentioning
confidence: 98%